VariantValidator: Accurate validation, mapping, and formatting of sequence variation descriptions. Issue 1 (17th October 2017) - Freeman, Peter J.; Hart, Reece K.; Gretton, Liam J.; Brookes, Anthony J.; Dalgleish, Raymond
Abstract: The Human Genome Variation Society (HGVS) variant nomenclature is widely used to describe sequence variants in scientific publications, clinical reports, and databases. However, the HGVS recommendations are complex and this often results in inaccurate variant descriptions being reported. The open‐source hgvs Python package (https://github.com/biocommons/hgvs ) provides a programmatic interface for parsing, manipulating, formatting, and validating of variants according to the HGVS recommendations, but does not provide a user‐friendly Web interface. We have developed a Web‐based variant validation tool, VariantValidator (https://variantvalidator.org/ ), which utilizes the hgvs Python package and provides additional functionality to assist users who wish to accurately describe and report sequence‐level variations that are compliant with the HGVS recommendations. VariantValidator was designed to ensure that users are guided through the intricacies of the HGVS nomenclature, for example, if the user makes a mistake, VariantValidator automatically corrects the mistake if it can, or provides helpful guidance if it cannot. In addition, VariantValidator has the facility to interconvert genomic variant descriptions in HGVS and Variant Call Format with a degree of accuracy that surpasses most competing solutions. Abstract : VariantValidator is a user‐friendly software tool designed to validate the syntax and parameters of DNA variant descriptions according to the HGVS Sequence Variant Nomenclature. VariantValidator ensures that users are guided through the intricacies of the HGVS nomenclature, e.g. if the user makes a mistake, VariantValidator automatically corrects the mistake if it can, or provides helpful guidance if it cannot. In addition, VariantValidator accurately interconverts between transcript variant descriptions and genomic variant descriptions in HGVS and Variant Call Format (VCF).